Synergistic association between hypercholesterolemia and the C46T factor XII polymorphism for developing premature myocardial infarction - Roldán, Vanessa; Corral, Javier; Marín, Francisco; Pineda, Javier; Vicente, Vicente; González-Conejero, Rocío (Thrombosis and Haemostasis, 2005)
Factor XII (FXII) plays a key role in both coagulation and fibrinolysis, thus its role in thrombotic processes is uncertain. Both genetic and environmental factors determine FXII plasma levels. A common C46T polymorphism in the Kozak region of F12 gene disturbs the translation of the protein leading to a significant reduction of FXII levels although its clinical significance is conflictive. We studied the F12 C46T polymorphism in 281 patients who had suffered from an acute myocardial infarction (MI) before 45-year-old and 550 control subjects from the same area. Serum levels of cholesterol, HDL, LDL, triglycerides and C reactive protein (CRP) were assayed in the MI group. The 46T allele slightly increased the risk to suffer from premature MI (OR:1.64; 95%CI: 1.14–2.37; p= 0.008). Moreover, patients carrying the 46T allele showed increased levels of CRP (p= 0.002). Interestingly, we found that the simultaneous presence of the 46T allele and hypercholesterolemia increases the risk to develop premature MI 2.26 times. The F12 C46T polymorphism, associated with a reduction of plasma FXII levels, seems to play a deleterious effect, predisposing the development of premature MI, especially in hypercholesterolemic patients. This effect could be associated with an increased pro-inflammatory state, as the 46T allele associates with high levels of CRP.
Keywords: Factor XII; genetic polymorphism; premature myocardial infarction; Hypercholesterolemia